MODERN CLUBS: TYPOLOGY AND INTERIOR DESIGN - Абизов, В. А.; Євтушик, Х. О. (Art and Design, 2023)
Purpose: identifying the characteristics of classifications and system-structural foundations of the typology of the architectural environment of modern clubs and the corresponding features of their design on the examples of specific institutions. Methodology. The research is based on a systemic approach, which makes it possible to study the macro and microstructure of a modern club as a fundamental basis for further studying the peculiarities of the interiors of institutions of this type. In addition, the methods of historical, comparative and typological analysis of the phenomenon of the modern club were used for the research. Results. Generalized historical prerequisites for the formation of clubs and peculiarities of the typology of entertainment establishments. The principles of classification of modern clubs according to: age and gender characteristics, professional orientation, social aspects, types of functions, location, target audience are revealed. Features of functional and design solutions of modern clubs are considered. Examples of the formation of a creative environment of entertainment and club establishments in the city of Kyiv according to age and gender, taking into account their location and stylistic features, are given. The scientific novelty of the study consists in the systematization and definition of the typology of leisure peculiarities and modern clubs according to various characteristics and the identification of the corresponding functional-spatial and artistic-image organization of their interiors. Features of the design of these institutions are given in accordance with the defined classifications by gender Practical significance. The proposed typology of modern clubs will enable future researchers and designers to study the features of each type of club and implement the principles of creating their harmonious and effective interior space. The research can be used in the design and operation of modern clubs.